Heritability of life‐history traits in the spruce budworm. Issue 1 (3rd June 2013) - Quezada‐García, Roberto; Bauce, Éric
Abstract The heritability of life‐history traits is of particular importance for insects that are very dependent on host conditions. Severe defoliation caused by the spruce budworm negatively impacts its food source, which in turn imposes environmental constraints on the insect. The heritability of those traits can help elucidate this species' evolutionary process. Heritability also helps identify which traits exhibit significant additive variance and can be key to understanding natural selection effects. Individuals were reared under laboratory conditions over three generations on an artificial diet. Heritability was estimated by parent–offspring regression. Fertility and fecundity demonstrated significant heritability followed by larval development, while pupal mass showed minimal heritable variation. These results suggest an important percent of additive variance in life‐history traits. This study contributes to our understanding of the relationship of this forest pest to its environmental conditions. This study also reveals an important genetic architectural structure of life‐history traits in the spruce budworm.